2016
DOI: 10.1021/jacs.5b11824
|View full text |Cite
|
Sign up to set email alerts
|

Transformative Evolution of Organolead Triiodide Perovskite Thin Films from Strong Room-Temperature Solid–Gas Interaction between HPbI3-CH3NH2 Precursor Pair

Abstract: We demonstrate the feasibility of a nonsalt-based precursor pair--inorganic HPbI3 solid and organic CH3NH2 gas--for the deposition of uniform CH3NH3PbI3 perovskite thin films. The strong room-temperature solid-gas interaction between HPbI3 and CH3NH2 induces transformative evolution of ultrasmooth, full-coverage perovskite thin films at a rapid rate (in seconds) from nominally processed rough, partial-coverage HPbI3 thin films. The chemical origin of this behavior is elucidated via in situ experiments. Perovsk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
160
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(168 citation statements)
references
References 23 publications
8
160
0
Order By: Relevance
“…Fig. 1b shows the morphology of the HPbI3 film, which is constituted by discontinuous, large sized grains and this phenomenon was also found in a recent report [40]. After reaction with CsI, the parent HPbI3 film turned yellow, and surprisingly, nanowires with diameters of 50-100 nm and lengths up to several micrometers tightly covered on the FTO glass could be observed ( Fig.…”
Section: Synthesis Of Cspbi3 Nanowiressupporting
confidence: 83%
See 1 more Smart Citation
“…Fig. 1b shows the morphology of the HPbI3 film, which is constituted by discontinuous, large sized grains and this phenomenon was also found in a recent report [40]. After reaction with CsI, the parent HPbI3 film turned yellow, and surprisingly, nanowires with diameters of 50-100 nm and lengths up to several micrometers tightly covered on the FTO glass could be observed ( Fig.…”
Section: Synthesis Of Cspbi3 Nanowiressupporting
confidence: 83%
“…Here, HPbI3 having a faster complete reaction with CsI could be attributed to an increased layer lattice, which facilitated the reaction with CsI to form CsPbI3 [38,40].…”
Section: Importance Of Hpbi3 Precursor In Synthesis Of Cspbi3 Nanowiresmentioning
confidence: 94%
“…It is reported that the HPbI 3 films show a hexagonal structure 20,34,36 . Upon increasing MACl content from 0 to 0.20, the low-angle peak around 11.7° shifts to a higher two theta value and the peak intensity increases significantly (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2, 3) 33,34 . Firstly, we tuned the thickness of perovskite films based on the HPbI 3 –CH 3 NH 2 reaction 20 by varying the substrate temperature (Supplementary Figs. 4, 5, 6, Supplementary Table 2 and Supplementary Note 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation